2017
DOI: 10.1038/srep40950
|View full text |Cite
|
Sign up to set email alerts
|

Unique Bacteria Community Composition and Co-occurrence in the Milk of Different Ruminants

Abstract: Lactation provides the singular source of nourishment to the offspring of mammals. This nutrition source also contains a diverse microbiota affecting the development and health of the newborn. Here, we examined the milk microbiota in water deer (Hydropotes inermis, the most primitive member of the family Cervidae), reindeer (Rangifer tarandus, the oldest semi-domesticated cervid), and the dairy goat (Capra aegagrus, member of the family Bovidae), to determine if common milk microbiota species were present acro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 53 publications
1
24
0
Order By: Relevance
“…In a study by Doyle et al (), Psychrobacter was commonly found during both indoor and outdoor seasons, but with higher numbers associated with milk samples from the indoor period. Halomonas has been observed in milk of different ruminants (Li et al ) and Janthinobacterium is often observed in spoiled milk (Eneroth et al ). Notably, among the top 11 OTUs found in our reference milk samples, there was a difference in the relative abundance of six OTUs depending on whether skimmed or whole milk samples were used.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study by Doyle et al (), Psychrobacter was commonly found during both indoor and outdoor seasons, but with higher numbers associated with milk samples from the indoor period. Halomonas has been observed in milk of different ruminants (Li et al ) and Janthinobacterium is often observed in spoiled milk (Eneroth et al ). Notably, among the top 11 OTUs found in our reference milk samples, there was a difference in the relative abundance of six OTUs depending on whether skimmed or whole milk samples were used.…”
Section: Discussionmentioning
confidence: 99%
“…This revealed dominance of the phylum Proteobacteria, particularly the genus Pseudomonas but also minor genera like Acinetobacter, Psychrobacter, Halomonas and Janthinobacterium. In a recent 12-month monitoring study by Li et al (2017), Pseudomonas, Lactococcus and Acinetobacter were identified as the most prevalent genera, with Acinetobacter and Pseudomonas representing the core microbiota. In a study by Doyle et al (2017), Psychrobacter was commonly found during both indoor and outdoor seasons, but with higher numbers associated with milk samples from the indoor period.…”
Section: Discussionmentioning
confidence: 99%
“…The milk microbiota has been mostly investigated in women (Hunt et al, 2011;Jost et al, 2013;Fitzstevens et al, 2016) and in cows (Oikonomou et al, 2014;Addis et al, 2016;Falentin et al, 2016); some studies were also conducted in other mammals such as goats, sheep, donkeys, buffalo, water deer, reindeer, or mice (Quigley et al, 2013;McInnis et al, 2015;Treven et al, 2015;Catozzi et al, 2017;Li et al, 2017;Soto Del Rio et al, 2017; Supplementary Table S1). Most studies on milk microbiota have investigated milk collected by manual expression, generally following thorough cleaning of nipples or teats (Oikonomou et al, 2012;Jost et al, 2013;Boix-Amoròs et al, 2016) (Figure 1).…”
Section: Milk Microbiota: Current Studies and Limitsmentioning
confidence: 99%
“…Human milk microbiota diversity has also been supported by culture-dependent approaches, which beyond the dominant genera Staphylococcus, Streptococcus, and Propionibacterium allowed the isolation of members of Bifidobacterium, Rothia, Enterococcus, Lactobacillus, or even obligate anaerobes such as Veillonella (Perez et al, 2007;Jost et al, 2013). Milk microbiota has also been investigated in other animals, including donkey, goat, sheep, water deer, reindeer, and water buffalo, although the number of studies is limited compared to that of studies of human and cow milk ( Supplementary Table S1), showing some overlap with human and cow milk microbiota (Figure 2; Castro et al, 2011;McInnis et al, 2015;Catozzi et al, 2017;Li et al, 2017;Soto Del Rio et al, 2017;Esteban-Blanco et al, 2019). Nevertheless, significant differences have been reported in the milk bacterial communities of different ruminants, such as water deer, reindeer, and goat, suggesting host microbial adaptation, although influence of environment and herd management should not be excluded (Li et al, 2017).…”
Section: A Core Milk Microbiota Universally Shared Between Hosts?mentioning
confidence: 99%
“…In human milk and the milk from different ruminants, a mammary gland-specific microbiome has been identified [33][34][35] . Goat (Capra hircus) milk production is of significant importance to the economy in many countries and offers many health benefits [36][37][38][39][40] ; this milk has demonstrated high microbial diversity in studies 41,42 and its consumption has shown potential benefits to intestinal microbiota 43 .…”
mentioning
confidence: 99%